Predictive Effect of System Inflammation Response Index for Progression of Chronic Kidney Disease in Non-Dialyzing Patient - Tang L; Deng Y; Lai J; Guo X; Liu P; Li S; Liu X (Dove Medical Press, 2023)
Leile Tang,1,* Ying Deng,2,* Jiahui Lai,2 Xinghua Guo,3 Peijia Liu,4 Shaomin Li,2 Xun Liu2 1Department of Cardiology, The Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong, People's Republic of China; 2Department of Nephrology, The Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong, People's Republic of China; 3Department of Rheumatology, Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, People's Republic of China; 4Department of Nephrology, Guangzhou Eighth People's Hospital, Guangzhou Medical University, Guangzhou, Guangdong, People's Republic of China*These authors contributed equally to this workCorrespondence: Xun Liu, Department of Nephrology, The Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong, 510630, People's Republic of China, Tel +8613711692006, Email naturestyle@163.comPurpose: Scant research has been conducted on the interplay between the systemic inflammation response index (SIRI) and chronic kidney disease (CKD). The present study endeavors to meticulously scrutinize the association between SIRI and renal function. Additionally, we aim to assess its efficacy in predicting the progression of CKD in non-dialysis patients.Patients and Methods: Adult patients with CKD who were not undergoing dialysis were enrolled, and follow-up data were obtained. Data from distinct groups were extracted and meticulously compared. A comprehensive analytical approach was adopted, including logistic regression analysis, Kaplan-Meier analysis, Cox proportional hazards regression analysis, and subgroup analysis.Results: Our study included 1420 patients, with a mean age of 61 ± 17 years, and 63% were male. 244 (17.2%) patients experienced the progression of CKD. As the level of ln(SIRI) increased, patients tended to be older, with a higher proportion of males, and increased prevalence rates of hypertension, stroke, heart failure, and progression of CKD. Additionally, the levels of baseline creatinine and C-reactive protein were elevated, while the levels of estimated glomerular filtration rate and hemoglobin decreased. Upon adjusting for demographic and biochemical variables, logistic regression analysis indicated that ln(SIRI) was independently associated with advanced CKD in pre-dialysis patients (OR=1.59, 95% CI: 1.29- 1.95, P< 0.001). Moreover, Cox proportional-hazard analysis revealed that ln(SIRI) independently predicted CKD progression (HR: 1.3, 95% CI: 1.07- 1.59, P=0.009). Conducting a subgroup analysis, we observed significant interactions between ln(SIRI) levels and gender (p< 0.001), age (p=0.046), and hypertension (p=0.028) in relation to the progression of CKD.Conclusion: Our study's findings demonstrate a significant association between SIRI and fundamental renal function, and independently establish a correlation between SIRI and the progression of CKD in pre-dialysis patients. These observations suggest that SIRI holds promise as a potential predictor for CKD progression.Keywords: system inflammation response index, progression, pre-dialysis, chronic kidney disease